Pembelajaran Kooperatif Tipe Jigsaw dalam Pembelajaran Fisika - Jawane Malau (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2014)
This research was conducted for the purpose of getting a clear and complete picture conserning the quality of teaching and learning process through eveloping and implementing jigsaw type cooparative learning model for subject of Thermodynamics. The quality of teaching and learning process can be viewed by positive response of university students towards thermodynamics subject using the implemented jigsaw type cooparative learning model. The subject of this research were students of high school class X, semester II in the academic year of 2011/2012, which were listed as learning tools needed for thermodynamics of jigsaw type cooparative learning model. The learning tool which were being developed consist of teaching materials, learning plan, and student worksheet. The research prosedure consisted of developing the tools of teaching and learning process, and the followed by realization of learning in class using the jigsaw type cooparative learning approach. The research instruments were to be observation sheet and student response questionaire towards the learning process. The reseach data were analyzed using percentage statistic. Based on the refection result towards the action which was planned beforehand and also the researh result discussion, it was found that the learning process of hermodynamics which was done by implementing the jigsaw type cooparative learning model can increase student activity in his study. Implementing the jigsaw type cooperative learning can increase the learning result of students. Most of the students who partisipated in the thermodynamics class agree and give a positive apreciation towards the implementation of cooperative learning model. They believe that with the learning group can help them overcoming the learning deterrent.